Family guide to mental illness and the law a practical handbook - Tashbook, Linda (New York Oxford University Press, 2019)
"When a loved one with mental illness comes into contact with the law, trying to advocate for them can be an overwhelming and frustrating endeavor. Mental illness adds a layer of complexity to legal processes, and the justice system can be downright bewildering, even for the most well-intentioned. How can families find out if their loved one is being mistreated or ignored, and how can they make sense of their rights under various laws and regulations? [This book] offers the nuts-and-bolts legal information and problem-solving steps families need. This...resource explains how common legal issues uniquely impact people with various forms of mental illness and what family members can do to help. Readers will learn how to help protect a loved one's job, housing, or medical care; participate in hearings about guardianship, involuntary commitment, bankruptcy, and more; assist in making financial arrangements; navigate federal laws surrounding the Family and Medical Leave Act, HIPAA, disability claims, and workers' compensation; and steer criminal proceedings away from jail and toward treatment. Beyond the legal system, this book also guides readers in interacting with officials and authorities, lobbying for better laws, and working with local governments towards improving policies that affect those with mental illness. Complete with real-world examples, [this book] provides practical advice and eases the feelings of isolation that often accompany loving someone with mental illness."--
Part 1. Health law. Health information privacy -- Disability benefits : SSDI and SSI -- Guardianship -- Psychiatric advance directives -- Involuntary commitment -- Professional misconduct -- Part 2. Criminal law. When police are called to help -- Negative police encounters, arrest, and jail -- Minor crimes -- Mental health court -- Criminal court trials and mental illness -- Mental illness in jails and prisons -- Criminal records and reputations -- Part 3. Employment law. Employee reputations and opportunities -- Employment discrimination -- Taking leave and being compensated -- Responses to employment termination -- Part 4. Consumer law. Owing money -- Families and finance -- Trusts -- Supportive money management -- Housing law -- Part 5. Death and the law. Missing persons -- Wrongful death -- Suicide law -- The wills of people with mental illness.
Keywords: Mental health laws -- United States -- Popular works; Mental health laws; United States; Popular works; Law for laypersons